Malignant psammomatous melanotic schwannoma of the spine: A component of Carney complex - Shields, Lisa B. E. (Medknow Publications Pvt Ltd, 2011)
BACKGROUND: Psammomatous melanotic schwannomas (PMS) of the spine may be a component of the Carney complex in 50% of cases and is inherited in an autosomal dominant manner. Most PMS are benign and frequently associated with lentiginous pigmentation; cardiac, cutaneous, or breast myxomas; endocrine overactivity; and cutaneous blue nevi. These tumors are characterized by melanin containing cells having ultrastructural characteristics of Schwann cells. CASE DESCRIPTION: Two patients had spinal PMS that were surgically resected with adjacent local radiotherapy, followed by local recurrence and metastasis. The aggressive nature of this tumor is reported. CONCLUSION: Spinal PMS are rarely malignant with local recurrence and distal metastases. Inquiry into the patient's and family members’ hereditary background for the Carney complex is important to avoid overlooking potential lethal associated abnormalities.